Normative value of upper extremity Y balance test in healthy subjects aged between 18 and 36 years from South India: A cross-sectional study - Arjun Pavithran; S. Rajasekar; Joshua Cleland; Varunkumar Ramkumar; Animesh Hazari (PLoS ONE, 2025)
Introduction The Upper Quarter Y Balance Test (UQYBT) is a validated tool used to assess unilateral upper extremity function in a closed kinetic chain. It evaluates parameters such as mobility, stability, and injury risk, and can inform rehabilitation planning. Normative data have been well established for adolescent and active adult populations in the United States. This study aims to establish normative UQYBT values for healthy adults aged 18–36 years in the Indian subcontinent. Methods A total of 190 healthy young adults (95 males and 95 females) aged 18–36 years who met the eligibility criteria were included. Baseline demographic data—age, height, weight, body mass index (BMI), and limb length—were collected. Participants performed the UQ-YBT by reaching in the inferolateral, medial, and superolateral directions using the three-reach box. Average reach distances were calculated for each limb, and composite scores (CS) were normalized using arm length. Results Age- and sex-specific reference values were established for both upper extremities and for average bilateral performance. Males demonstrated significantly greater reach distances than females; however, the difference decreased after normalization for limb length. Age-related variations were observed, with participants aged 26–30 years achieving the highest normalized reach scores (p < 0.05). Conclusion The age- and sex-specific normative values obtained from this study can serve as benchmarks for assessing shoulder mobility and stability among healthy Indian adults aged 18–36 years.